2020
DOI: 10.3390/ijerph17145126
|View full text |Cite
|
Sign up to set email alerts
|

Parental Factors Associated with Obesity in Korean Adolescents

Abstract: Parental characteristics can influence adolescent obesity. However, the influence of parental characteristics on obesity may differ depending on the adolescent’s sex. This study evaluated parental characteristics that were associated with obesity in male and female adolescents. This study involved the secondary data analysis of cross-sectional survey data that were collected from June to September 2015. The study subjects included 1621 eighth-grade students. The study variables included sex, age, body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Participants with higher income and from cities had higher nutrition literacy than participants from villages and lower income. Since most of our study participants were females this could reflectpatriarchy [24] than sociodemographic variables. Income gap and geographical locations of Palestinian villages could not justify discrepancies in terms of access to healthcare Many Palestinian villages are close to cities centers, and despite the fact Palestinian cities have higher concentration of nutrition care services, reaching out to these centers is feasible with the strong transportation system in the West Bank [25].…”
Section: Discussionmentioning
confidence: 99%
“…Participants with higher income and from cities had higher nutrition literacy than participants from villages and lower income. Since most of our study participants were females this could reflectpatriarchy [24] than sociodemographic variables. Income gap and geographical locations of Palestinian villages could not justify discrepancies in terms of access to healthcare Many Palestinian villages are close to cities centers, and despite the fact Palestinian cities have higher concentration of nutrition care services, reaching out to these centers is feasible with the strong transportation system in the West Bank [25].…”
Section: Discussionmentioning
confidence: 99%
“…Important moderators of parental underestimation of children’s overweight or obesity status were found to include parent weight, child gender, and the assessment method used (visual versus nonvisual) [ 40 ]. Furthermore, identified obesity-associated factors among Korean male and female students included underestimation and overestimation of male adolescent weight by fathers, whereas factors among females included underestimation of female adolescent weight by fathers [ 41 ]. The study concluded that parental involvement in obesity interventions could aid in preventing adolescent obesity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, identified obesity-associated factors among Korean male and female students included underestimation and overestimation of male adolescent weight by fathers, whereas factors among females included underestimation of female adolescent weight by fathers [ 41 ]. The study concluded that parental involvement in obesity interventions could aid in preventing adolescent obesity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood and adolescent obesity are rapidly becoming a global epidemic [ 20 ]. Multiple studies have investigated the effect of parental factors on adolescent weight and physical activity, mostly showing poor parental influence leads to poorer nutritional habits and poorer exercise habits that persist into adulthood [ 50 ]. A systematic review study on the relationship between parental and child obesity found that there was a parent–child association in obesity, with stronger associations noted in older children [ 47 ].…”
Section: Introductionmentioning
confidence: 99%